Analysis of Business Strategy Using SWOT and QSPM Method at Topten Printing in Metro City - Adafi Imtiyaz Abiyyi; Rr Erlina; Ahmad Faisol (Harmony Management: International Journal of Management Science and Business, 2025)
This study examines Topten Printing, a printing company based in Metro City that offers diverse printing services characterized by competitive pricing, high-quality output, and efficient service. The research addresses the challenge of sustaining competitiveness amid rising market competition and evolving customer preferences. The objective is to analyze the company’s existing competitive strategies and propose viable alternatives for future growth. Employing a qualitative approach through a case study method, the research utilizes SWOT analysis and the Quantitative Strategic Planning Matrix (QSPM) to assess internal and external factors influencing the business. The results reveal that Topten Printing’s key strengths lie in its affordable pricing, reliable print quality, and prompt service delivery. However, the company also faces notable weaknesses, including a limited workforce and insufficient engagement on social media platforms. Opportunities exist in the growing demand for printed materials and government initiatives supporting micro, small, and medium enterprises (MSMEs), whereas significant threats stem from digital transformation trends and raw material price volatility. The synthesis of findings indicates that to enhance its market position, Topten Printing should implement a growth-oriented strategy focused on increasing production capacity by hiring freelance workers and intensifying social media marketing efforts. In conclusion, strengthening human resources and expanding digital marketing activities are essential steps for Topten Printing to maintain competitiveness and seize market opportunities in an increasingly dynamic business environment.